PRIMA Task Force as a Government Program on the Covid-19 Health Protocol in Padang City - Putri Febri Wialdi; Roni Ekha Putera (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
To speed up the handling of COVID-19 in Padang City, the Padang City Government together with relevant stakeholders in this case is FORKOPIMDA (Regional Leadership Coordination Forum) Padang City created the SATGAS PRIMA (Community Behavior Change Task Force) program, in which the project leader in the Civil Service Police Unit. Padang City in synergy with relevant stakeholders. Starting from the low awareness of the people of Padang City in carrying out health protocols which resulted in Padang City is included in the ranks of 13 regencies/cities that contributed the highest number of active Covid-19 cases in Indonesia with these findings, the central government through the spokesman for the national Covid-19 handling gave a warning to the Padang City Government regarding the Covid-19 handling system carried out. In this study, researchers used the synergy theory proposed by Irwan Noor, Triana Rahmawati, and Ike Manusmawati. Where in developing the concept of synergy, two important elements are needed, namely communication and coordination. This research was conducted with a descriptive qualitative method, where the data collection system used was through interviews and documentation studies. The results of the study show that this program can be a tactical step for the Padang City Government in reducing the number of COVID-19 cases in the Padang City area also through this program the Civil Service Police Unit as a project leader gets the best award number 2 from the Governor of West Sumatra.